Metathesis in Natural Product Synthesis 2010
DOI: 10.1002/9783527629626.ch2
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products Containing Medium‐Sized Nitrogen Heterocycles Synthesized by Ring‐Closing Alkene Metathesis

Abstract: The formation of carbon-carbon bonds is a crucial issue in organic synthesis. Out of all methodologies available, the metathesis reaction has, over the past decade, evolved as one of the most useful tools in this field to rapidly construct the skeleton of carba-and heterocyclic molecules [1]. Key step of the metathesis reaction entails the metal-catalyzed redistribution of two carbon-carbon double bonds by a scission-recombination process [2]. Among various applications of the metathesis reaction, ring-closing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 100 publications
(78 reference statements)
0
16
0
Order By: Relevance
“…Nitrogen-containing heterocycles are found in a wide range of natural products and biologically active synthetic compounds (8)(9)(10)(11)(12)(13)(14)(15). In addition, nitrogen-containing heterocycles constitute a common structural unit of many marketed drugs (16,17).…”
Section: Pharmaceutical Chemistry Department Faculty Of Medicine Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen-containing heterocycles are found in a wide range of natural products and biologically active synthetic compounds (8)(9)(10)(11)(12)(13)(14)(15). In addition, nitrogen-containing heterocycles constitute a common structural unit of many marketed drugs (16,17).…”
Section: Pharmaceutical Chemistry Department Faculty Of Medicine Andmentioning
confidence: 99%
“…Effective drugs should be able to treat both stages of the disease or at least one of them. Pentamidine (9) and suramin (10) are used in early stages of African trypanosomiasis, whereas eflornithine (12) or the combination nifurtimox (13)-eflornithine (12) is approved for second-stage treatment. Melarsoprol (11), an arsenical drug with high toxicity, is also approved in later stages ( Fig.…”
Section: Antitrypanosomal Activitymentioning
confidence: 99%
“…[2 -6] Recent progress in various metal-catalyzed ring-forming reactions has facilitated access to these classically otherwise difficult-to-make ring systems. [7][8][9][10][11][12][13][14] In particular, olefin-metathesis mediated transformations, [15][16][17][18][19][20][21][22][23][24][25][26][27][28] either in tandem or in sequence with other named and unnamed reactions, [29,30] have provided rapid access to several structurally embellished entities accommodating the core ring systems. However, comparatively less attention has been paid to develop synthetic methodologies that simultaneously address incorporation of functionalities within the core ring system.…”
Section: Introductionmentioning
confidence: 99%
“…2 Their structurally unfavorable conformational states brought about by entropic and enthalpic effects, means that their synthesis primarily relies on ring-closing metathesis reactions. 3 Although the number of synthetic examples of eight-membered heterocycles has increased in natural product synthesis, that of nine-membered rings, especially those with multiple heteroatoms within the ring framework, is limited. 1, 3 Recently, we reported a synthetic route towards tetracyclic compounds containing a nine-membered sultam, wherein we demonstrated that a cobalt-alkyne complex-mediated cyclization could serve as a powerful approach for the synthesis of nine-membered heterocycles containing nitrogen and sulfur atoms.…”
mentioning
confidence: 99%
“…3 Although the number of synthetic examples of eight-membered heterocycles has increased in natural product synthesis, that of nine-membered rings, especially those with multiple heteroatoms within the ring framework, is limited. 1, 3 Recently, we reported a synthetic route towards tetracyclic compounds containing a nine-membered sultam, wherein we demonstrated that a cobalt-alkyne complex-mediated cyclization could serve as a powerful approach for the synthesis of nine-membered heterocycles containing nitrogen and sulfur atoms. 4 Motivated by the rapid construction of novel nine-membered ring frame-works, we attempted to clarify the substrate scope and limitations by modifying the ring size and constituent elements.…”
mentioning
confidence: 99%